Designing a Community-Driven Circular Value Chain for Plastic Upcycling in Indonesia’s TPS 3R Systems - Indra Lukmana Putra; Triesti Candrawati Candrawati; Peni uspitasari; Yekie Senja Oktora; Mohammad Junus (Reviu Accounting, Business & Organizations, 2026)
Research Objective – To design an integrated Circular Value Chain Model for upcycling plastic waste through community-based TPS 3R systems, enhancing economic value, social impact, and environmental sustainability. Research       Method - Mixed-methods approach: qualitative case study with in-depth interviews, field observations, and document analysis at TPS 3R Basama; quantitative simulation for economic feasibility (NPV, IRR, Payback Period) and environmental impact estimation. Research Findings – An applicable Circular Value Chain Model for TPS 3R that identifies existing barriers (technical, institutional, market), with simulations of economic value added and landfill residue reduction through upcycling into high-value products. ​Theoretical and Policy Implications – Theoretically strengthens circular economy frameworks by adapting plastic packaging waste supply chains community level upcycling; policy-wise, models for local governments to integrate TPS 3R into sustainable waste management strategies, supporting SDGs 11, 12, and 13. Research Novelty – Develops a context-specific Circular Value Chain Model for TPS 3R in Indonesia, addressing gaps value chains for plastic upcycling—transforming linear waste management into community-driven circular economies with validated prototypes